Elevated ST2 Distinguishes Incidences of Pediatric Heart and Small Bowel Transplant Rejection. Issue 3 (11th December 2015) - Mathews, L. R.; Lott, J. M.; Isse, K.; Lesniak, A.; Landsittel, D.; Demetris, A. J.; Sun, Y.; Mercer, D. F.; Webber, S. A.; Zeevi, A.; Fischer, R. T.; Feingold, B.; et al.
Abstract : Elevated serum soluble (s) suppressor of tumorigenicity‐2 is observed during cardiovascular and inflammatory bowel diseases. To ascertain whether modulated ST2 levels signify heart (HTx) or small bowel transplant (SBTx) rejection, we quantified sST2 in serially obtained pediatric HTx (n = 41) and SBTx recipient (n = 18) sera. At times of biopsy‐diagnosed HTx rejection (cellular and/or antibody‐mediated), serum sST2 was elevated compared to rejection‐free time points (1714 ± 329 vs. 546.5 ± 141.6 pg/mL; p = 0.0002). SBTx recipients also displayed increased serum sST2 during incidences of rejection (7536 ± 1561 vs. 2662 ± 543.8 pg/mL; p   = 0.0347). Receiver operator characteristic (ROC) analysis showed that serum sST2 > 600 pg/mL could discriminate time points of HTx rejection and nonrejection (area under the curve [AUC] = 0.724 ± 0.053; p = 0.0003). ROC analysis of SBTx measures revealed a similar discriminative capacity (AUC = 0.6921 ± 0.0820; p = 0.0349). Quantitative evaluation of both HTx and SBTx biopsies revealed that rejection significantly increased allograft ST2 expression. Pathway and Network Analysis of biopsy data pinpointed ST2 in the dominant pathway modulated by rejection and predicted tumor necrosis factor‐α and IL‐1β as upstream activators. In total, our data indicate that alloimmune‐associated pro‐inflammatory cytokines increase ST2 during rejection. They also demonstrate that routine serum sST2 quantification, potentially combined with other biomarkers, should be investigated further to aid in the noninvasive diagnosis of rejection. Abstract : Biopsy‐ and serum‐based assessments of pediatric transplant recipients reveal that pro‐inflammatory cytokines associated with rejection may increase allograft and serum levels of suppressor of tumorigenicity 2 and suggest the potential of the measurement of this protein to aid noninvasive diagnosis of rejection.